‘Pemimpin Itu Jagoan’: Memahami Definisi Pemimpin Perspektif Anak Usia Dini - Fitria Ulfah (Universitas Darunnajah, 2025)
This study aims to reveal that early childhood has a perspective related to leadership, which is interpreted differently depending on the child's perspective. The method in this study is a focused ethnography conducted for approximately 2 months. The research subjects were all students in groups A and B of Candra Kindergarten-Bandung. Data collection techniques used observation and semi-formal interviews with children. Meanwhile, the data analysis technique used a grounded theory approach. The study illustrates that early childhood has its own perspective regarding leaders, but children do not define leaders in a segregated manner, that leaders are male or female. Children define leaders with adjectives such as